2004
DOI: 10.2139/ssrn.617346
|View full text |Cite
|
Sign up to set email alerts
|

Do Gasoline Prices Converge in a Unified Europe with Non-Harmonized Tax Rates?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Stated differently, convergence to the LOOP for a product means that its time series of relative prices as defined in is mean reverting or stationary (Dreher and Krieger, 2005:10). The common approach to examine price convergence is to apply a unit root test to examine the stationarity of the price differential series.…”
Section: An Overview Of the Data And Empirical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Stated differently, convergence to the LOOP for a product means that its time series of relative prices as defined in is mean reverting or stationary (Dreher and Krieger, 2005:10). The common approach to examine price convergence is to apply a unit root test to examine the stationarity of the price differential series.…”
Section: An Overview Of the Data And Empirical Analysismentioning
confidence: 99%
“…Unfortunately, the Augmented Dickey‐Fuller (ADF) test, which is the commonly used unit root test for a single time series, has low power, causing it to overly reject the stationarity hypothesis of a time series (Cecchetti et al. , 2002:1087; Dreher and Krieger, 2005:12; Fan and Wei, 2005:21). To address this problem, Levin, Lin and Chu (2002) (LLC) have shown that the use of a panel unit root test can significantly increase the power of a unit root test.…”
Section: An Overview Of the Data And Empirical Analysismentioning
confidence: 99%
“…In terms of consumer surplus and welfare, there is an expectation of fair pricing on the part of consumers, where price differentials are wholly attributed to transportation costs, taxation, and other explicit barriers. In addition to this, consumer price convergence can shift an energy tax burden onto the producers, which leads to a competitive disadvantage for firms in high-tax regions (Dreher and Krieger, 2005;Suvankulov et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Rejection of the unit root hypothesis also indicates that relative centrality scores follow a random walk. This means that deviation among the three regions' time series becomes permanent (Dreher and Krieger 2005). In addition, the Levin-Lin-Chu test assumes a common autoregressive parameter for all panels to deal with autocorrelation.…”
Section: Resultsmentioning
confidence: 99%